Impact of state management on the development of agricultural production: security aspect - Prots, Roman (Global Prosperity, 2022)
The article examines the significant impact of state management on the development of agricultural production. State management forms the basic framework for effective activity in the agricultural sector through the development and implementation of policies aimed at supporting farmers and agricultural enterprises. This includes providing subsidies, tax incentives, grants, and other financial tools that help reduce production costs and increase the competitiveness of products in both domestic and external markets. Additionally, the state establishes standards of quality and safety for products, which ensures consumer trust and opens new markets for distribution. Infrastructure development, coordinated by the state, is a key factor in enhancing the efficiency of agricultural activities. The construction and modernization of transportation networks, irrigation systems, and energy supply ensure efficient logistics, reduce transportation costs, and increase the productivity of farms. Investments in modern technologies help stabilize the agricultural sector, allowing farmers to adapt to changing market conditions and climatic challenges, ensuring long-term production growth. Education and scientific research hold an indispensable place in the state strategy for the development of agriculture. Funding for agricultural research and the introduction of innovative technologies increase yield and product quality. Educational programs and training for farmers enhance their qualifications and adaptability to new challenges such as climate change or the emergence of new pests. Support for scientific institutions promotes sustainable and innovative growth in agricultural production. Regulation and control by the state guarantee market stability and protect the interests of all participants in the agricultural process. Establishing clear rules and norms prevents monopolization, corruption, and other negative phenomena, ensuring fair competition and protecting the rights of farmers and consumers. State authorities monitor the market, analyze trends, and respond to external challenges, allowing for the rapid adaptation of agricultural sector development strategies. A comprehensive approach by the state to managing agriculture creates a stable and predictable environment for investors and entrepreneurs, promoting sustainable and innovative growth in agricultural production.